PROCESS FOR RECOVERY CHROMIUM FROM ELECTROCHEMICAL MACHINING WASTE BY ACID LEACHING AND CHEMICAL PRECIPTATION. - Asst. Prof Dr. Saad K. Shather Dr. Hijran Z. Toama, Shahad W. Hamed (International Journal of Research Science and Management, 2018)
The waste from ECM is hazardous solid wastes due to the presence of specific heavy metals such as chromium, iron, nickel, lead and molybdenum. Hence, recovery of these metals not only saves the environment, but also has the advantages of financial and economic returns. So recovery of chromium from this waste was investigated. Chromium was recovered by using hydrometallurgical method via acid leaching and chemical precipitation. The effect of leaching parameters of time, solution concentration, and leaching temperature were found to be significant. The optimum process operating parameters were established as follows: (7 M) sulfuric acid concentration, (60 min) leaching time, and the temperature was (25 Co ). Leaching solutions at the optimum experiments were used for chemical precipitation, chromium was selectively converted into insoluble component by adding sodium hydroxide NaOH at pH (8).